Difficulties in learning mathematics among primary school students from the perspective of subject teachers - Hassan, Asst.L. Chopi Rauf Hassan; Kri, Asst.L. Bafrin Gharib Ghafoor Kri Ghafoor (Sulaimani Journal for Humanities, 2026)
This research, entitled "challenges facing mathematics learning among basic education students from the Perspective of Mathematics Teachers," aims to identify the obstacles impeding the learning of mathematics among students in basic education as perceived by mathematics teachers. The research population consists of all mathematics teachers in public and non-governmental schools in the Sulaymaniyah Governorate for the academic year 2025–2026 who are currently in service. The research sample comprises 180 teachers of both genders, selected via simple random sampling. Researchers prepared and used a questionnaire to collect data based on previous studies. It consists of six domains (objectives of teaching mathematics, mathematics textbooks in terms of content and form, methods and strategies used, teacher-related problems, student-related problems, and assessment methods), with eight items allocated for each domain. Key statistical tools used include the Pearson correlation coefficient, weighted mean, and percentage. The results revealed the existence of challenges in all six domains. Finally, in light of the results, the researchers presented several recommendations, including 1) clarifying the objectives of studying mathematics for students at the beginning of the semester and throughout the term. 2) Presenting information step-by-step through the mathematics textbook according to the students' academic stages.
Keywords: Challenges; Mathematics; Learning; Basic Education